Using logistics models to study the most important factors affecting diabetes by type of disease - Kawther Saeed Taha; Drakhshan Jalal Hassan (QALAAI ZANIST JOURNAL, 2020)
In this research, analysis of the discrimination of logistics is used, and the maximum likelihood method was used to estimate the parameters of the logistic model. This study has been done on diabetic patents visiting laila kassim diabetes center in hawler city in 2018. The data has been collected from both types of diabetes (type I and type II) via filing on questionnaire during personal interview with every patients and historical records. The main objective of this research is to study the main risk factors that differentiate between type I and type II and through using statistical analysis of the discrimination of logistics we can discover the effect of either factor on increasing risk (incidence) of diabetic. We concluded in this study, the model of logistic discrimination is appropriate in the study of the factors affecting for both types of diabetes and found that the estimated parameters of the logistic model are significant through the test (Wald). The two variables (the age of incidence of diabetes and blood sugar level) are significant factors on dependable variable which represent the incidence of diabetes while the other variables have no effect. And the correct classification ratio is )83.6%(.